(untitled) (Scientific journal of the Fergana State University, 2023)
Using inductively coupled plasma mass spectrometry (ICP-MS) on the device (ICP-MS) AT 7500, the elemental composition of root and seed samples of Peganum harmala plants growing in the Fergana region of the Fergana region was studied in detail for the first time. 42 elements were quantitatively determined in the composition of the roots and seeds of the Peganum harmala plant. It has been established that the roots of the plant contain 40 elements, and the seeds - 42 elements. A natural tendency for the amount of an element to decrease as its mass increases is shown. It has been observed that the amount of heavy elements in the roots of the Peganum harmala plant is somewhat higher than the amount of heavy elements in the seeds.